2001
DOI: 10.1021/om010483v
|View full text |Cite
|
Sign up to set email alerts
|

Nanosized, Starlike Silicon Compounds. Synthesis and Optical Properties of Tris[(tert-butyldimethylsilyl)oligothienylenedimethylsilyl]methylsilanes

Abstract: Starlike molecules with arms consisting of a tert-butyldimethylsilyloligothienylenedimethylsilyl unit, MeSi[SiMe 2 (T) n SiMe 2 (t-Bu)] 3 (7-11; n ) 2-6, T ) thienylene) were prepared by the reactions of tris(chlorodimethylsilyl)methylsilane, which was chosen as a core, with the tert-butyldimethylsilyl-substituted lithiooligothienylenes used for construction of the arms. UV-visible absorption and fluorescence properties of 7-11 have been studied in a dioxane solution. The molecules 7-11 showed high fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…It should be noted that bromination of tert butyldimethyl silylbi , ter , and quaterthiophenes on treatment with NBS in chloroform for 15 h in 84 to 96% yields has been reported. 19 Presumably, in the case of methyltrithienyl silane 2, which contains monothienyl groups, no bromi nation in chloroform took place due to too low reactivity of the proton in position 5 of the thiophene residue in a low polarity solvent, while the insufficient stability of the Si-C thiophene bond precluded the use of more polar sol vents. It is known 18 that the reactivity of the 2(5) proton in α,α oligothiophenes markedly increases with an in crease in conjugation (the number of thiophene rings).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that bromination of tert butyldimethyl silylbi , ter , and quaterthiophenes on treatment with NBS in chloroform for 15 h in 84 to 96% yields has been reported. 19 Presumably, in the case of methyltrithienyl silane 2, which contains monothienyl groups, no bromi nation in chloroform took place due to too low reactivity of the proton in position 5 of the thiophene residue in a low polarity solvent, while the insufficient stability of the Si-C thiophene bond precluded the use of more polar sol vents. It is known 18 that the reactivity of the 2(5) proton in α,α oligothiophenes markedly increases with an in crease in conjugation (the number of thiophene rings).…”
Section: Resultsmentioning
confidence: 99%
“…Starthiophene derivatives with one central silicon atom linked to three oligothiophene units has attracted a considerable interest since a discovery of strong uorescence of the star-like molecules that have a regular arrangement of Si-Si bonds and bithienylene units. 68 Luponosov et al 69 synthesized star-shaped oligothiophenesilanes 3a,b by rstly lithiation of 5-hexyl-2,2 0 -bithiophene 1 or 5-hexyl-2,2 0 :5 0 ,2 00 -terthiophene 2, respectively, followed by reaction with methyltrichlorosilane (Scheme 1). This work was extended to the synthesis of some different dentritic oligothiophenes, via Suzuki coupling reaction.…”
Section: Ssms With Acyclic Coresmentioning
confidence: 99%
“…2,4,3, In a 300 mL two-necked flask equipped with a stirrer, reflux condenser, and dropping funnel was placed a solution of 2-thienylmagesium bromide prepared from 3.768 g (0.155 mol) of magnesium and 25.340 g (0.155 mol) of 2-bromothiophene in 200 mL of THF. To this was added 0.831 g (1.59 mmol) of NiCl 2 (dppe) and then 6.466 g (34.5 mmol) of 2,4,6-trichloro-1,3,5-triazine in 30 mL of THF.…”
Section: General Proceduresmentioning
confidence: 99%
“…We have reported the synthesis and optical properties of several types of the nanosized starlike molecules: the molecules bearing a methyltris(silyl)silane unit as a core and the arms consisting of a regular alternating arrangement of an SieSi bond and bithienylene unit [3], the starlike molecules with the same core and oligothienylene units as the arms [4], and the molecules including 1,3,5-tris-and 1,2,4,5-tetrakis(silyl)benzene as a core and bithienyleneedisilanylene units in the arms [5]. We have found that the starlike molecules show novel optical properties, such as high fluorescence quantum yields and long lifetimes of the excited state.…”
Section: Introductionmentioning
confidence: 99%